Analisis Pendahuluan Metabolit Sekunder dari Kalus Mahkota Dewa (Phaleria macrocarpa [Scheff.] Boerl.) - Erlindha Gangga; Henita Asriani; Linda Novita (Fakultas Farmasi Universitas Pancasila, 2007)
Callus is a cell mass which is formed by cell tissues and formed in explants surface or explants slice which divide them continuously in a controlled condition. With tissue culture method, the aim in using callus is for reproduce new plants to get the secondary metabolite which match with the secondary metabolite from the origin plants. Mahkota dewa (Phaleria macrocarpa [Scheff.] Boerl.), from Thymelaceae family is a very useful plant which can be used for medicine. Its leaves and seed's skin are the most important parts that usually used. In this experiment, Mahkota’s seed is planted in germination media to get a sterile plant, and then from the plant, we take the leaves for callus initiation. We do a phytochemical filtering, TLC, and HPLC tests with this callus that we produced then we compared the result with Mahkota Dewa's leaves. From the phytochemical filtering result we found that both of them have alkaloid secondary metabolite, flavonoid saponin, tannin, steroid/triterpenoid. We also found some chromatograms which are similar in TLC and HPLC.